Problematika Norma Landasan Partai Politik Indonesia - Emy Hajar Abra (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2021)
The interpretation of political parties in the political party law can be used as the heart of the political party law. Unfortunately, the problem of norms related to the basis of political parties is not properly emphasized, on the contrary, it becomes multiple interpretations on the basis of political parties which should be the only source of law in determining the basis of political parties in Indonesia. This clearly causes the weak implementation of the law on political parties. This can certainly be seen how each political party can provide a multi-basic basis on the basis of norms as stated in the political party law. In fact, if examined more deeply, the law on political parties does not give room for multiple interpretations when referring to the definition of political parties.